2009
DOI: 10.1177/0163278708328736
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Multimodal Training for Healthcare Professionals at an AIDS Education and Training Center

Abstract: There is an ongoing need for continuing professional education (CPE) in the rapidly changing field of HIV care, but the best instructional methods remain a subject of debate. This study assessed the effects of training at an AIDS Education and Training Center (AETC) over an 18-month period. Health care professionals (HCP) who attended more than one training event showed small but significant improvements over time in HIV-related clinical practice behaviors. The type of training also predicted self-reported pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Similarly, of the 444 responses with valid data on intent to change practice, 374 (84.2%) indicated the learner would change how she or he worked with HIV-infected patients, whereas 41 (7.3%) indicated the learner would not change, and 29 (6.5%) designated the question as not applicable. However, no significant correlation was observed between average change in self-rated knowledge and change in PAT score in any year of training, corroborating the findings by Cook, Friedman, Lord, and Bradley-Springer (2009) that self-reported knowledge change may not be a reliable predictor of objectively measured knowledge change.…”
Section: Quantitative Impact Datasupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, of the 444 responses with valid data on intent to change practice, 374 (84.2%) indicated the learner would change how she or he worked with HIV-infected patients, whereas 41 (7.3%) indicated the learner would not change, and 29 (6.5%) designated the question as not applicable. However, no significant correlation was observed between average change in self-rated knowledge and change in PAT score in any year of training, corroborating the findings by Cook, Friedman, Lord, and Bradley-Springer (2009) that self-reported knowledge change may not be a reliable predictor of objectively measured knowledge change.…”
Section: Quantitative Impact Datasupporting
confidence: 77%
“…Indeed, Cook et al (2009) demonstrated that objective change in knowledge and skills, measured by preand post-testing, is predictive of behavior change in HIV clinical training of health care professionals. Our evaluation did not measure behavior change more thoroughly in an effort to balance the rigor of optimal program evaluation methodology with real-world evaluation priorities, such as limiting interference with clinical training and operating within resource constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Some evaluators consider self-assessed gains in knowledge to represent Kirkpatrick's level 1 data (Werth, 2009;Wisher, 2004) whereas others treat it as level 2 data (Al-Jishi, Khalek, & Hamdy, 2009;Baker & Brooks, 2005;Bartlett & Sherry, 2004;Cook, Friedman, Lord, & Bradley-Springer, 2009;McLean & Moss, 2003). However, Kirkpatrick's definition of level 2 assessment clearly requires measuring the actual learning of a topic, not the perception of how much was learned, as can be seen in Kirkpatrick's guidelines on how to assess learning outcomes: ''(1) Measure knowledge, skill and/or attitudes before and after the training.…”
Section: Perceived Learning As Another Type Of Reactionmentioning
confidence: 99%
“…Consequently, training on brief risk screening methods that do not require much of providers' time and brief risk-reduction interventions can enhance comfort, skills, and motivation of providers. 57 The AIDS Education and Training Centers, 58 which operate nationwide, provide excellent education and training programs for health care providers treating persons living with HIV/AIDS and can be instrumental for this purpose.…”
Section: Discussionmentioning
confidence: 99%